A preliminary investigation into environmental temperature and relative humidity during international transportation of sport horses - White, C.; Gehring, R.; Hall, C. (DCA Report; Nr. 044, 2014)
The globalisation of the equine industry has led to a substantial increase in the transportation of sport horses. Research to date has primarily focused on the impact of transportation on health and welfare however, there is currently very little research investigating the environmental conditions experienced during the transportation of sport horses. This preliminary study set out to record and analyse the ambient temperature (°C) and relative humidity (%) in seven horse boxes, transporting a total of eighteen horses during the journey back from an FEI CCI**** event in Pau, France to the UK. The journey consisted of approximately 20.50 hours of road transport and 1.50 hours of ferry transport, over a total mean distance of 1401.14±100.62 km. No significant difference in overall temperature between the road and ferry stages of the journey was found (P>0.05). However, as the journey was lengthy and incorporated travel during both day and night, this was perhaps a surprising finding. A difference in relative humidity, however, was found between horse boxes for the whole journey (P<0.001), the ferry journey (P<0.001) and when comparing road travel in France to the ferry journey (P=0.037). The mean relative humidity levels obtained for the entire journey were found to be 74.62% (±4.43); however, these levels increased during ferry travel (mean 80.67% (±7.01). Heat and humidity levels seen in individual horse boxes varied considerably during the journey and depending on type of travel (road vs. ferry). These changes may be due to differences in individual horse box design and the impact on ventilation and air flow. However, further research is needed to establish the implications of horse box design and to develop optimal travel conditions for sport horses. LP: Heat and humidity levels in individual horse boxes were found to vary considerably during the journey with differences according to the stage of the journey. Humidity levels were found to be highest during ferry travel and variations between horse boxes for both temperature and humidity levels were found.